Italy : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2011)
Based on the economic literature, various policy measures and institutions in the product and labor markets that increase growth and employment are studied. From a cross-country approach, this study finds a significant relationship between Vertical Fiscal Imbalances (VFIs) and fiscal performance in OECD countries. Different measures of vertical imbalance are used. To assess the impact of a vertical gap, a panel equation is estimated that is related to general government primary balance to vertical balance, spending decentralization, covariates, and interaction terms.